Northpointe Chalet a contemporary retelling of Northanger Abbey - Smith, Debra White; Austen, Jane 1775-1817. (Minneapolis, Minnesota Bethany House, a division of Baker Publishing Group, 2018)
When a lively group of customers visit Kathy Moore's café, new friendships--and romance--ensue. When she learns of a mystery in their past, Kathy takes on the role of amateur detective, but will her digging do more damage than good.
Keywords: Austen, Jane -- 1775-1817. -- Ficti; Women booksellers -- Ficti; Clergy -- Fiction; Mansions -- Fiction; Colorado -- Fiction